A Case Report of Wire-localised Excision of Impalpable Recurrent Papillary Thyroid Carcinoma and Discussion of Wire-guided Excision in the Head and Neck Pathology - Farrell, Eric; Speaker, Richard; O’Driscoll, Donal; Skinner, Liam (Current Medical Imaging, 2024)
Introduction/Background:Wire localisation techniques are used widely for precision surgery in many specialities. This convenient technique has not yet become mainstream in the field of head and neck surgery. With limited space and many vital structures coursing through the head and neck region, pathological nodes that are difficult to palpate can be a challenge for clinicians.Case Presentation:A patient with a history of papillary thyroid cancer treated with surgery and radioactive iodine had a single pathological node detected on ultrasound surveillance. An isolated recurrence of papillary thyroid carcinoma was confirmed. An excisional biopsy was performed using ultrasound wire guidance to successfully remove the diseased node with minimal morbidity.Conclusion:Wire-guided lymph node excision biopsy is a safe and effective method that can be applied to multiple pathologies. As of yet, it is not routine practice to employ this technique. Larger studies would increase the generalisability and safety profile of this technique in the head and neck region.
Keywords: Lymph node biopsy